1999
DOI: 10.1002/(sici)1097-4687(199909)241:3<237::aid-jmor6>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Constructional morphology and mode of attachment of the trunk of Corynosoma cetaceum (Acanthocephala: Polymorphidae)

Abstract: Dead specimens of Corynosoma cetaceum were used to describe the trunk musculature of this species and to infer the use of the trunk as a secondary holdfast. Inferences were based on trunk muscle arrangement, changes in trunk shape, size and distribution of spines, and geometry of tegument thickness. The foretrunk of C. cetaceum is swollen and forms a spiny disk that is bent ventrally. The disk is flattened by several groups of muscles not described previously, which seem able to finely adjust the disk surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The body of adult acanthocephalans is anchored at the intestinal wall of their de®nitive hosts by the presoma (Taraschewski 1989a(Taraschewski , b, 2000Taraschewski et al 1989). Additionally, in some species the trunk serves as an organ of attachment (Aznar et al 1999).…”
Section: Introductionsupporting
confidence: 79%
“…The body of adult acanthocephalans is anchored at the intestinal wall of their de®nitive hosts by the presoma (Taraschewski 1989a(Taraschewski , b, 2000Taraschewski et al 1989). Additionally, in some species the trunk serves as an organ of attachment (Aznar et al 1999).…”
Section: Introductionsupporting
confidence: 79%
“…Specimens of C. cetaceum examined in the present paper agree in general terms with the characteristics that define the species; however, some differences in the number of proboscis hook rows (20-21 versus 18-9) and in the number of hooks per row (13-15 versus 12-13 or 14-16) were observed. The ventrally transverse folds delimiting a blunt lobe between the fore-and hind-trunks in the female, described by Aznar et al (1999bAznar et al ( , 2002b, were also observed in cystacanths in the present study.…”
Section: Locusmentioning
confidence: 99%
“…Corynosoma hamanni was mostly found in the duodenum of Antarctic seals, but about 3% of the component population was found in the pyloric region of the stomach (Zdzitowiecki, 1984). On the other hand, adult Corynosoma cetaceum have repeatedly been reported from the stomach and duodenum of at least 3 species of cetaceans from the Southern Hemisphere (Brownell, 1975;Kagei et al, 1976;Figueroa and Puga, 1990;Torres et al, 1992;Aznar et al, 1994;Corcuera et al, 1995;Andrade et al, 1997;Aznar et al, 1999).The presence of adult acanthocephalans in the stomachs of marine mammals is puzzling because the digestive and absorptive functions in these hosts are well separated; the stomach is involved only in digestive functions as in other mammals (Gaskin, 1978;Berta and Sumich, 1999). This raises the question over whether Corynosoma reported from the stomach might represent recently recruited worms or worms located in an abnormal habitat (Crompton, 1973;Kennedy, 1985).…”
mentioning
confidence: 99%
“…Corynosoma hamanni was mostly found in the duodenum of Antarctic seals, but about 3% of the component population was found in the pyloric region of the stomach (Zdzitowiecki, 1984). On the other hand, adult Corynosoma cetaceum have repeatedly been reported from the stomach and duodenum of at least 3 species of cetaceans from the Southern Hemisphere (Brownell, 1975;Kagei et al, 1976;Figueroa and Puga, 1990;Torres et al, 1992;Aznar et al, 1994;Corcuera et al, 1995;Andrade et al, 1997;Aznar et al, 1999).…”
mentioning
confidence: 99%